Complete permanent mandibular dentition of early Homo from the upper Burgi Member of the Koobi Fora Formation, Ileret, Kenya. Issue 131 (June 2019) - Grine, Frederick E.; Leakey, Meave G.; Gathago, Patrick N.; Brown, Frank H.; Mongle, Carrie S.; Yang, Deming; Jungers, William L.; Leakey, Louise N.
Abstract: The KNM-ER 64060 dentition derives from a horizon that most likely dates to between 2.02 and 2.03 Ma. A proximate series of postcranial bones (designated KNM-ER 64061) derives from the same siltstone unit and may be associated with the dentition, but their separation on the surface of the site leaves some room for doubt. KNM-ER 64060 is one of fewer than ten hominin specimens from the Early Pleistocene of East Africa that comprises a full or nearly complete mandibular dentition. Its taxonomic attribution is potentially significant, especially if the postcranial elements are related. At least three, and probably four hominin species, including Paranthropus boisei and Homo erectus (= H. ergaster ), are known at about this time in East Africa. Other penecontemporaneous fossils have been referred to a single, highly variable species, H. habilis, or two taxa, namely H. habilis and H. rudolfensis . Although the weight of evidence supports the attribution of these specimens to two species, there is notable lack of agreement over the assignation of individual fossils. We take a conservative approach and group all such specimens under the designation "early Homo sp." for comparative purposes. KNM-ER 64060 is clearly attributable to Homo rather than Paranthropus . The preponderance of the evidence suggests that the affinities of KNM-ER 64060 are with fossils assigned to the early Homo sp. category rather than with H. erectus . This is indicated by the overall sizes of the KNM-ER 64060 canine, premolar and molar crowns, the size relationships of the P3 to P4, the relative narrowness of its premolar crowns, the cusp proportions of the M1 and especially those of the M2 and M3, and seemingly the possession of a two-rooted P4 . Some of these comparisons suggest further that among the fossils comprising the early Homo sp. sample, the KNM-ER 64060 dentition exhibits greater overall similarity to specimens such as OH 7 and OH 16 that represent Homo habilis sensu stricto.